The Effect of Firm Performance, Financial Distress, and Operational Complexity on Audit Report Lag with Corporate Governance Mechanism and Audit Quality as Moderation - Naibaho, Eduard Ary Binsar; Dewanti (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
The purpose of this study is to examine the effect of firm performance, financial distress and complexity on audit report lag with corporate governance mechanisms and audit quality as moderating variables. Firm performance proxy Tobin's and ROA, financial distress proxy Altman's, managerial ownership, board size, and audit quality. The research uses secondary data from 128 companies in Indonesia, Australia and New Zealand, which are included in the office of manufacture and mining in the S&P Capital IQ for the period 2018-2022. The sample collection technique uses a purposive sampling method. This research found that company performance and financial distress had no effect, while complexity had an effect on audit report lag. Managerial ownership has an effect on Tobin, financial distress, and complexity on audit report lag, but managerial ownership has no effect on ROA. The size of the board of directors has an effect on Tobin but has no effect on ROA, financial distress, and complexity on audit report lag. Audit quality has no effect on company performance and complexity but does affect financial distress and audit report lag.